Differences in objective balance outcomes between elite female rugby players with and without a history of lateral ankle sprain - Martin, M.; Tawa, N.; Leibbrandt, D. C.; Louw, Q. A. (African Journal for Physical Activity and Health Sciences, 2021)
This study was conducted to examine differences in objective balance outcomes of female rugby players with (injury group; n = 12) and without (control group: n = 19) a history of lateral ankle sprains. The injured and the uninjured ankles in the previously injured players were also compared. An analytical cross-sectional design was used in this study, which was conducted at the Western Province Rugby Football Union`s (WPRFU) High Performance Centre in Cape Town, South Africa. The Noraxon myoPressureTM (Zebris) pressure plate was used to measure objective dynamic balance using COP (centre of pressure) parameters, namely sway area (SA), COP speed (COP sp), and time-to-boundary (TTB), during single-leg catch-and-throw, single-leg jump landing, and side stepping. The ankle sprain group had statistically significant differences in the SA outcome for the tasks catch-and-throw (p=0.04) and side step (p=0.01) compared with the control group. Regarding the TTB outcome in the treatment category, significant results for catch-and-throw (p=0.02) and side step (0=0.01) tasks were found in contrast to the controls. Further results yielded a substantial difference in COP speed outcome for the side step task (p=0.01) among players with a known history of ankle injury compared with the control category. Rugby players with a history of ankle sprain have altered dynamic balance and poor postural stability. Sway area and COP speed during side-step and catch-and-throw tasks can be used as practical measures of objective dynamic balance in rugby.